Shift of Eco-Feminism towards Posthumanist Future: The Doris Lessing’s Sci-fi Turn in Writing - Huang, Yuwei; Tan, Qi (Journal of Theory and Practice of Social Science, 2023)
After more than two decades of literary endeavors, Doris Lessing embarked on a captivating odyssey into the realm of science fiction, delving deep into the intricate tapestry that intertwines women and nature which features Eco-feminism during the 1980s. It dawned upon her that eco-feminism's ultimate destination transcends mere admonishment of androcentrism and anthropocentrism; rather, it aspires to forge an idyllic utopia for both humanity and our fragile ecosystems for the future. Nevertheless, this visionary landscape is not easily forged and demanding meticulous consideration of myriad factors due to the fact that the "rampant" development of technology alters the way we live in and we perceive the world. Therefore, the Doris Lessing sensed the change in literary realm and explored the futuristic path for human society which worth our attention. The thesis is going to analyze Lessing's writing shift and her key sci-fi work The Marriage Between Zone Three, Four and Five to figure out her path of building up the harmonious future and the significance of posthumanist turn.